Financial Constraints and Firm Innovation Decision: The Roles of Corporate Governance and Risk Diversification - Hong, Cancheng; Ren, Ting (Emerging markets finance & trade, 2025)
Firm innovation decision is subject to the influence of financial constraints, but the mechanism through which this impact occurs remains unclear. Using a nationwide representative survey data set of private firms in China in 2016, we first identified the strengthening effect of financial constraints on firm innovation decision, and further demonstrated the influence of corporate governance and risk diversification on such a relationship. The results show that firms tend to increase investment in innovation to improve operations when facing tighter financial constraints. Firms with suboptimal corporate governance and better conditions of risk diversification tend to adopt riskier innovation strategy to cope with tighter financial constraints.